Transcriptional analysis in bacteriophage Fc02 of Pseudomonas aeruginosa revealed two overlapping genes with exclusion activity - Ramírez-Sánchez, Irais; Magos-Castro, Marco; Guarneros, Gabriel (Frontiers in Microbiology, 2023)
Little is known about the gene expression program during the transition from lysogenic to lytic cycles of temperate bacteriophages in Pseudomonas aeruginosa. To investigate this issue, we developed a thermo-sensitive repressor mutant in a lysogen and analyzed the phage transcriptional program by strand-specific RNA-Seq before and after thermo-induction. As expected, the repressor gene located on the phage DNA forward strand is transcribed in the lysogen at the permissive temperature of 30°C. Upstream the repressor gene, we noticed the presence of two overlapped ORFs apparently in the same transcript. One ORF is a gene that encodes a protein of 7.9 kDa mediating the exclusion of various super-infecting phages. The other ORF, placed in an alternate reading frame with a possible AUG initiation codon at 25 nucleotide downstream of the AUG of the first gene, is expected to encode a 20.7 kDa polypeptide of yet an unknown function. Upon lifting repression at 40°C, the transcription of an operon which is involved in the lytic cycle is started from a promoter on the reverse phage DNA strand. The first gene in the operon is a homolog of the antirepresor ner, a common gene in the lysis–lysogeny regulation region of other phages. Interestingly, the next gene after ner is gene 10 that on the reverse strand overlaps the overlapped gene olg1 on the forward strand. Curiously, gene 10 expression also shows superinfection exclusion. Strand-specific RNA-Seq also has uncovered the transcription succession of gene modules expressed during the phage lytic stage. The conservation of overlapped genes with similar functions may be evolutionarily selected.